Anti-aging fiber and preparation method thereof
The anti-aging fiber, prepared through coaxial electrostatic spinning of specific emulsions, addresses the limitations of existing fibers by integrating antistatic, flame retardant, antibacterial, and moisture-absorbing capabilities, improving its performance and application scope.
Patent Information
- Application Number
- CN202411657196.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Existing fibers lack integrated antistatic, flame retardant, antibacterial, and moisture-absorbing capabilities, limiting their application in high-performance materials beyond traditional textiles.
An anti-aging fiber is prepared by coaxial electrostatic spinning of polyacrylic acid emulsion and ultraviolet absorption polyacrylate emulsion, utilizing polymerized pyrrole and olefin mixed liquids with 3,5-di-tert-butyl-4-hydroxybenzyl alcohol to enhance conductivity, flame retardancy, and antibacterial properties, and incorporating carboxyl groups for moisture absorption.
The fiber exhibits improved antistatic, flame retardant, antibacterial, and moisture-absorbing properties, enhancing its performance in industrial applications and expanding its use beyond traditional textiles.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of fibers, in particular to an anti-aging fiber and a preparation method thereof. Background Art
[0002] Fiber refers to a material with a very small fineness, a diameter of only a few microns to a maximum of tens of microns, and a length hundreds or even thousands of times larger than the diameter, and with a certain flexibility and strength. Textile fiber refers to the fiber used to make textiles, that is, the unit body with appropriate length, flexibility and strength used to make yarn and fabric in textile production. There are many ways to classify textile fibers, and they can be divided into two categories according to their source: natural fibers and chemical fibers; natural fibers can be divided into plant fibers and animal fibers, and chemical fibers can be divided into artificial fibers and synthetic fibers.
[0003] Chemical fiber is a fiber obtained by chemical treatment and processing. Chemical fiber is not affected by the weather and location. With the development of science and technology, new varieties of chemical fiber continue to emerge, fiber performance continues to improve, and new application areas of clothing fibers continue to expand. In the field of industrial application, it has long gone beyond the scope of traditional textile industry and is replacing traditional materials and high-performance materials such as steel, hardware, and wood building materials, expanding to a broader application market and high-tech fields. This article introduces an anti-aging fiber with antistatic, flame retardant, antibacterial and moisture-absorbing capabilities. Summary of the invention
[0004] The purpose of the present invention is to provide an anti-aging fiber and a preparation method thereof to solve the problems existing in the prior art.
[0005] The invention discloses an anti-aging fiber, which is prepared by coaxial electrostatic spinning of polyacrylic acid emulsion and ultraviolet absorption polyacrylate emulsion.
[0006] The polyacrylic acid emulsion is prepared by polymerizing acrylic acid, propylene glycol and propenyl-1,3-sultone.
[0007] The ultraviolet absorbing polyacrylate emulsion is prepared by polymerizing a pyrrole mixed liquid and an olefin mixed liquid and then reacting the mixture with 3,5-di-tert-butyl-4-hydroxybenzyl alcohol.
[0008] A method for preparing an anti-aging fiber, the method for preparing an anti-aging fiber mainly comprises the following preparation steps: (1) Mix the pyrrole mixed solution, olefin mixed solution, xylene and catalyst in a mass ratio of 1:4-6:25-35:0.06-0.1, stir at 130-140°C and 200-300 r / min for 4-6 hours, heat to 145-155°C, continue to react for 100-140 minutes, and then adjust the pH to 6.5-7.5 with dimethylethanolamine to obtain a polyacrylate emulsion; (2) The polyacrylate emulsion and 3,5-di-tert-butyl-4-hydroxybenzyl alcohol were mixed uniformly in a mass ratio of 10 to 14:1, and then 0.01 to 0.02 times the mass of the polyacrylate emulsion was added with sodium acetate, and the mixture was stirred at 210 to 220°C, 200 to 300 r / min, and reacted for 10 to 12 hours under nitrogen protection, and then cooled to room temperature to obtain a UV absorbing polyacrylate emulsion; (3) Mix acrylic acid, propylene glycol, xylene and azobisisobutyronitrile in a molar ratio of 4-6:1:25-35:0.03-0.05, stir at 130-140°C and 200-300 r / min for 4-6 hours, heat to 145-155°C, add propylene glycol and an amount of propenyl-1,3-sultone of the same mass, and continue the reaction for 100-140 minutes to obtain a polyacrylic acid emulsion; (4) Using UV-absorbing polyacrylate emulsion as the shell solution and polyacrylic acid emulsion as the core solution, coaxial electrospinning was performed, the fibers were allowed to stand for 6 to 8 hours, and then naturally cooled to room temperature to obtain anti-aging fibers.
[0009] As an optimization, the olefin mixed liquid in step (1) is prepared by uniformly mixing methyl methacrylate, diethyl allyl phosphate, isooctyl acrylate, methyl methacrylate, methacrylate and butyl acrylate in a mass ratio of 8-10:2-4:4-6:5-7:12-16.
[0010] As an optimization, the pyrrole mixture in step (1) is prepared by uniformly mixing 1-allyl-1H-pyrrole, pyrrole and 1-(dimethylamino)pyrrole in a mass ratio of 1:3 to 5:1.
[0011] As an optimization, the catalyst in step (1) is prepared by mixing azobisisobutyronitrile and ferric chloride in a mass ratio of 1:1.
[0012] As an optimization, the liquid flow rate of the shell solution in step (4) is 0.9-1.1 ml / h.
[0013] As an optimization, the liquid flow rate of the core solution in step (4) is 0.2-0.3 ml / h.
[0014] As an optimization, the coaxial electrospinning parameters of step (4) are as follows: liquid flow rate of 0.2-0.3 ml / h, receiving distance of 14-16 cm, receiving speed of 9-11 r / min, and spinning voltage of 22-26 kV.
[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: When preparing the anti-aging fiber, the present invention comprises the following steps: polymerizing a pyrrole mixed liquid and an olefin mixed liquid and then reacting the mixed liquid with 3,5-di-tert-butyl-4-hydroxybenzyl alcohol to obtain an ultraviolet absorbing polyacrylate emulsion; polymerizing acrylic acid, propylene glycol and propylene-1,3-sultone to obtain a polyacrylic acid emulsion; and coaxially electrospinning the polyacrylic acid emulsion and the ultraviolet absorbing polyacrylate emulsion to obtain the anti-aging fiber.
[0016] First, when preparing the anti-aging fiber, the present invention polymerizes the pyrrole mixed liquid and the olefin mixed liquid and then reacts with 3,5-di-tert-butyl-4-hydroxybenzyl alcohol to obtain the ultraviolet absorption polyacrylate emulsion; the pyrrole mixed liquid and the olefin mixed liquid are polymerized together, and polypyrrole as a conductive polymer can absorb and disperse static charge, thereby reducing the accumulation of static electricity and achieving the antistatic effect; and the phosphate ester can chemically react with the active free radicals generated in the combustion process, thereby inhibiting the generation and conduction of the free radicals and preventing the effective contact between oxygen and the combustion material, so that the activity of the combustion material surface can be reduced, the formation of flames and the rate of combustion reaction can be slowed down, thereby playing a flame retardant role, and at the same time, the organic phosphorus can also release during the combustion process. A large amount of phosphorus-containing compounds can generate phosphates with carbon on the surface of the burning material at high temperature to form a phosphate protective layer, which covers the surface of the burning material and plays a role in heat insulation and oxygen isolation, preventing the continued combustion of the burning material and improving the flame retardant ability of the material. 3,5-di-tert-butyl-4-hydroxybenzyl alcohol is connected to the main chain of polyacrylate through ester exchange. 3,5-di-tert-butyl-4-hydroxybenzyl alcohol is a hindered phenol. The hydroxyl group is restricted by spatial obstacles, and the hydrogen atom is very easy to fall off from the original molecular structure to achieve the proton-donating effect and combine with peroxy radicals, alkyl radicals, hydroxyl radicals, etc., resulting in the loss of original activity and the termination of oxygen aging reaction, thereby achieving anti-aging effect.
[0017] Secondly, acrylic acid, propylene glycol and propylene-1,3-sultone are polymerized to obtain polyacrylic acid emulsion; polyacrylic acid emulsion and ultraviolet absorption polyacrylate emulsion are coaxially electrospun to obtain anti-aging fiber; polyacrylic acid emulsion is rich in carboxyl groups and can react with ammonia to achieve the effect of deodorization. At the same time, since carboxyl groups are hydrophilic groups, they can absorb moisture and thus be antistatic; the sultone on the synthesized polyacrylic acid emulsion can react with tertiary amines to generate quaternary ammonium and sulfonate ions. The quaternary ammonium cations adsorb negatively charged bacteria through electrostatic forces, hydrogen bonds, and hydrophobic binding between surfactant molecules and protein molecules, and accumulate on the cell wall to produce a chamber resistance effect, resulting in the inhibition of bacterial growth and death; at the same time, its hydrophobic alkyl group can also react with the hydrophilic group of bacteria to change the permeability of the membrane, and then lyse the cell structure, causing the dissolution and death of the cell, achieving the antibacterial effect, and the quaternary ammonium salt has hydrophilic groups and non-polar groups, which enables it to absorb moisture in the air. This hygroscopicity helps to reduce the resistivity of the material surface and enhance the antistatic ability of the material. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example 1
[0019] A method for preparing anti-aging fiber mainly comprises the following preparation steps: (1) Methyl methacrylate, diethyl allyl phosphate, isooctyl acrylate, methyl methacrylate, methacrylate and butyl acrylate were mixed in a mass ratio of 8:2:4:5:12 to obtain an olefin mixture; 1-allyl-1H-pyrrole, pyrrole and 1-(dimethylamino)pyrrole were mixed in a mass ratio of 1:3:1 to obtain a pyrrole mixture; the pyrrole mixture, olefin mixture, xylene, azobisisobutyronitrile and ferric chloride were mixed in a mass ratio of 1:4:25:0.03:0.03, stirred at 130°C and 200 r / min for 4 h, heated to 145°C, reacted for 100 min, and then the pH was adjusted to 6.5 with dimethylethanolamine to obtain a polyacrylate emulsion; (2) The polyacrylate emulsion and 3,5-di-tert-butyl-4-hydroxybenzyl alcohol were mixed uniformly in a mass ratio of 10:1, and then 0.01 times the mass of the polyacrylate emulsion of sodium acetate was added, and the mixture was stirred at 200 r / min for 10 hours at 210°C under nitrogen protection, and then cooled to room temperature to obtain a UV absorbing polyacrylate emulsion; (3) Acrylic acid, propylene glycol, xylene and azobisisobutyronitrile were mixed in a molar ratio of 4:1:25:0.03, stirred at 130°C and 200 r / min for 4 h, heated to 145°C, and then an amount of propylene glycol and acryl-1,3-sulfonate in an amount equal to that of propylene glycol was added, and the reaction was continued for 100 min to obtain a polyacrylic acid emulsion; (4) Using UV-absorbing polyacrylate emulsion as the shell solution, the liquid flow rate is 0.9 ml / h; using polyacrylic acid emulsion as the core solution, the liquid flow rate is 0.2 ml / h, and electrospinning is performed; the liquid flow rate is 0.2 ml / h, the receiving distance is 14 cm, the receiving speed is 9 r / min, and the spinning voltage is 22 kV; standing for 6 hours, and naturally cooling to room temperature to obtain anti-aging fibers. Example 2
[0020] A method for preparing anti-aging fiber mainly comprises the following preparation steps: (1) Methyl methacrylate, diethyl allyl phosphate, isooctyl acrylate, methyl methacrylate, methacrylate and butyl acrylate were mixed in a mass ratio of 9:3:5:6:14 to obtain an olefin mixture; 1-allyl-1H-pyrrole, pyrrole and 1-(dimethylamino)pyrrole were mixed in a mass ratio of 1:4:1 to obtain a pyrrole mixture; the pyrrole mixture, olefin mixture, xylene, azobisisobutyronitrile and ferric chloride were mixed in a mass ratio of 1:5:30:0.04:0.04, stirred at 135°C and 250 r / min for 5 h, heated to 150°C, reacted for 120 min, and then the pH was adjusted to 7 with dimethylethanolamine to obtain a polyacrylate emulsion; (2) The polyacrylate emulsion and 3,5-di-tert-butyl-4-hydroxybenzyl alcohol were mixed uniformly in a mass ratio of 12:1, and then 0.015 times the mass of the polyacrylate emulsion of sodium acetate was added, and the mixture was stirred at 250 r / min for 11 hours at 215°C under nitrogen protection, and then cooled to room temperature to obtain a UV absorbing polyacrylate emulsion; (3) acrylic acid, propylene glycol, xylene and azobisisobutyronitrile were mixed in a molar ratio of 5:1:30:0.04, stirred at 135°C and 250 r / min for 5 h, heated to 150°C, and then an amount of propylene glycol and acryl-1,3-sulfonate in an amount equal to that of propylene glycol was added, and the reaction was continued for 120 min to obtain a polyacrylic acid emulsion; (4) Using UV-absorbing polyacrylate emulsion as the shell solution, the liquid flow rate is 1 ml / h; using polyacrylic acid emulsion as the core solution, the liquid flow rate is 0.25 ml / h, and electrospinning is performed; the liquid flow rate is 0.25 ml / h, the receiving distance is 15 cm, the receiving speed is 10 r / min, and the spinning voltage is 24 kV; standing for 7 hours, and naturally cooling to room temperature to obtain anti-aging fibers. Example 3
[0021] A method for preparing anti-aging fiber mainly comprises the following preparation steps: (1) Methyl methacrylate, diethyl allyl phosphate, isooctyl acrylate, methyl methacrylate, methacrylate and butyl acrylate were mixed in a mass ratio of 10:4:6:7:16 to obtain an olefin mixture; 1-allyl-1H-pyrrole, pyrrole and 1-(dimethylamino)pyrrole were mixed in a mass ratio of 1:5:1 to obtain a pyrrole mixture; the pyrrole mixture, the olefin mixture, xylene, azobisisobutyronitrile and ferric chloride were mixed in a mass ratio of 1:6:35:0.05:0.05, stirred at 140°C and 300 r / min for 6 h, heated to 155°C, reacted for 140 min, and then the pH was adjusted to 7.5 with dimethylethanolamine to obtain a polyacrylate emulsion; (2) The polyacrylate emulsion and 3,5-di-tert-butyl-4-hydroxybenzyl alcohol were mixed uniformly in a mass ratio of 14:1, and then 0.02 times the mass of the polyacrylate emulsion of sodium acetate was added, and the mixture was stirred at 220°C and 300 r / min for 12 hours under nitrogen protection, and then cooled to room temperature to obtain a UV absorbing polyacrylate emulsion; (3) acrylic acid, propylene glycol, xylene and azobisisobutyronitrile were mixed in a molar ratio of 6:1:35:0.05, stirred at 140°C and 300 r / min for 6 h, heated to 155°C, and then an amount of propylene glycol and acryl-1,3-sulfonate in an amount equal to that of propylene glycol was added, and the reaction was continued for 140 min to obtain a polyacrylic acid emulsion; (4) Using UV-absorbing polyacrylate emulsion as the shell solution, the liquid flow rate is 1.1 ml / h; using polyacrylic acid emulsion as the core solution, the liquid flow rate is 0.3 ml / h, and electrospinning is performed; the liquid flow rate is 0.3 ml / h, the receiving distance is 16 cm, the receiving speed is 11 r / min, and the spinning voltage is 26 kV; standing for 8 hours, and naturally cooling to room temperature to obtain anti-aging fibers.
[0022] Comparative Example 1 A method for preparing anti-aging fiber mainly comprises the following preparation steps: (1) Methyl methacrylate, diethyl allyl phosphate, isooctyl acrylate, methyl methacrylate, methacrylate and butyl acrylate were mixed in a mass ratio of 9:3:5:6:14 to obtain an olefin mixture; the olefin mixture, xylene, azobisisobutyronitrile and ferric chloride were mixed in a mass ratio of 5:30:0.04:0.04, stirred at 135°C and 250 r / min for 5 h, heated to 150°C, reacted for 120 min, and then the pH was adjusted to 7 with dimethylethanolamine to obtain a polyacrylate emulsion; (2) The polyacrylate emulsion and 3,5-di-tert-butyl-4-hydroxybenzyl alcohol were mixed uniformly in a mass ratio of 12:1, and then 0.015 times the mass of the polyacrylate emulsion of sodium acetate was added, and the mixture was stirred at 250 r / min for 11 hours at 215°C under nitrogen protection, and then cooled to room temperature to obtain a UV absorbing polyacrylate emulsion; (3) acrylic acid, propylene glycol, xylene and azobisisobutyronitrile were mixed in a molar ratio of 5:1:30:0.04, stirred at 135°C and 250 r / min for 5 h, heated to 150°C, and then an amount of propylene glycol and acryl-1,3-sulfonate in an amount equal to that of propylene glycol was added, and the reaction was continued for 120 min to obtain a polyacrylic acid emulsion; (4) Using UV-absorbing polyacrylate emulsion as the shell solution, the liquid flow rate is 1 ml / h; using polyacrylic acid emulsion as the core solution, the liquid flow rate is 0.25 ml / h, and electrospinning is performed; the liquid flow rate is 0.25 ml / h, the receiving distance is 15 cm, the receiving speed is 10 r / min, and the spinning voltage is 24 kV; standing for 7 hours, and naturally cooling to room temperature to obtain anti-aging fibers.
[0023] Comparative Example 2 A method for preparing anti-aging fiber mainly comprises the following preparation steps: (1) Methyl methacrylate, isooctyl acrylate, methyl methacrylate, methacrylate and butyl acrylate were mixed in a mass ratio of 9:5:6:14 to obtain an olefin mixture; 1-allyl-1H-pyrrole, pyrrole and 1-(dimethylamino)pyrrole were mixed in a mass ratio of 1:4:1 to obtain a pyrrole mixture; the pyrrole mixture, olefin mixture, xylene, azobisisobutyronitrile and ferric chloride were mixed in a mass ratio of 1:5:30:0.04:0.04, stirred at 135°C and 250 r / min for 5 h, heated to 150°C, reacted for 120 min, and then the pH was adjusted to 7 with dimethylethanolamine to obtain a polyacrylate emulsion; (2) The polyacrylate emulsion and 3,5-di-tert-butyl-4-hydroxybenzyl alcohol were mixed uniformly in a mass ratio of 12:1, and then 0.015 times the mass of the polyacrylate emulsion of sodium acetate was added, and the mixture was stirred at 250 r / min for 11 hours at 215°C under nitrogen protection, and then cooled to room temperature to obtain a UV absorbing polyacrylate emulsion; (3) acrylic acid, propylene glycol, xylene and azobisisobutyronitrile were mixed in a molar ratio of 5:1:30:0.04, stirred at 135°C and 250 r / min for 5 h, heated to 150°C, and then an amount of propylene glycol and acryl-1,3-sulfonate in an amount equal to that of propylene glycol was added, and the reaction was continued for 120 min to obtain a polyacrylic acid emulsion; (4) Using UV-absorbing polyacrylate emulsion as the shell solution, the liquid flow rate is 1 ml / h; using polyacrylic acid emulsion as the core solution, the liquid flow rate is 0.25 ml / h, and electrospinning is performed; the liquid flow rate is 0.25 ml / h, the receiving distance is 15 cm, the receiving speed is 10 r / min, and the spinning voltage is 24 kV; standing for 7 hours, and naturally cooling to room temperature to obtain anti-aging fibers.
[0024] Comparative Example 3 A method for preparing anti-aging fiber mainly comprises the following preparation steps: (1) Methyl methacrylate, diethyl allyl phosphate, isooctyl acrylate, methyl methacrylate, methacrylate and butyl acrylate were mixed in a mass ratio of 9:3:5:6:14 to obtain an olefin mixture; 1-allyl-1H-pyrrole and pyrrole were mixed in a mass ratio of 1:4 to obtain a pyrrole mixture; the pyrrole mixture, olefin mixture, xylene, azobisisobutyronitrile and ferric chloride were mixed in a mass ratio of 1:5:30:0.04:0.04, stirred at 135°C and 250 r / min for 5 h, heated to 150°C, reacted for 120 min, and then the pH was adjusted to 7 with dimethylethanolamine to obtain a polyacrylate emulsion; (2) The polyacrylate emulsion and 3,5-di-tert-butyl-4-hydroxybenzyl alcohol were mixed uniformly in a mass ratio of 12:1, and then 0.015 times the mass of the polyacrylate emulsion of sodium acetate was added, and the mixture was stirred at 250 r / min for 11 hours at 215°C under nitrogen protection, and then cooled to room temperature to obtain a UV absorbing polyacrylate emulsion; (3) acrylic acid, propylene glycol, xylene and azobisisobutyronitrile were mixed in a molar ratio of 5:1:30:0.04, stirred at 135°C and 250 r / min for 5 h, heated to 150°C, and then an amount of propylene glycol and acryl-1,3-sulfonate in an amount equal to that of propylene glycol was added, and the reaction was continued for 120 min to obtain a polyacrylic acid emulsion; (4) Using UV-absorbing polyacrylate emulsion as the shell solution, the liquid flow rate is 1 ml / h; using polyacrylic acid emulsion as the core solution, the liquid flow rate is 0.25 ml / h, and electrospinning is performed; the liquid flow rate is 0.25 ml / h, the receiving distance is 15 cm, the receiving speed is 10 r / min, and the spinning voltage is 24 kV; standing for 7 hours, and naturally cooling to room temperature to obtain anti-aging fibers.
[0025] Comparative Example 4 A method for preparing anti-aging fiber mainly comprises the following preparation steps: (1) Methyl methacrylate, diethyl allyl phosphate, isooctyl acrylate, methyl methacrylate, methacrylate and butyl acrylate were mixed in a mass ratio of 9:3:5:6:14 to obtain an olefin mixture; 1-allyl-1H-pyrrole, pyrrole and 1-(dimethylamino)pyrrole were mixed in a mass ratio of 1:4:1 to obtain a pyrrole mixture; the pyrrole mixture, olefin mixture, xylene, azobisisobutyronitrile and ferric chloride were mixed in a mass ratio of 1:5:30:0.04:0.04, stirred at 135°C and 250 r / min for 5 h, heated to 150°C, reacted for 120 min, and then the pH was adjusted to 7 with dimethylethanolamine to obtain a polyacrylate emulsion; (2) acrylic acid, propylene glycol, xylene and azobisisobutyronitrile were mixed in a molar ratio of 5:1:30:0.04, stirred at 135°C and 250 r / min for 5 h, heated to 150°C, and then an amount of propylene glycol and acryl-1,3-sulfonate in an amount equal to that of propylene glycol was added, and the reaction was continued for 120 min to obtain a polyacrylic acid emulsion; (3) Using polyacrylate emulsion as shell solution, the liquid flow rate is 1 ml / h; using polyacrylic acid emulsion as core solution, the liquid flow rate is 0.25 ml / h, electrospinning; the liquid flow rate is 0.25 ml / h, the receiving distance is 15 cm, the receiving speed is 10 r / min, and the spinning voltage is 24 kV; standing for 7 hours, and naturally cooling to room temperature to obtain anti-aging fibers.
[0026] Comparative Example 5 A method for preparing anti-aging fiber mainly comprises the following preparation steps: (1) Methyl methacrylate, diethyl allyl phosphate, isooctyl acrylate, methyl methacrylate, methacrylate and butyl acrylate were mixed in a mass ratio of 9:3:5:6:14 to obtain an olefin mixture; 1-allyl-1H-pyrrole, pyrrole and 1-(dimethylamino)pyrrole were mixed in a mass ratio of 1:4:1 to obtain a pyrrole mixture; the pyrrole mixture, olefin mixture, xylene, azobisisobutyronitrile and ferric chloride were mixed in a mass ratio of 1:5:30:0.04:0.04, stirred at 135°C and 250 r / min for 5 h, heated to 150°C, reacted for 120 min, and then the pH was adjusted to 7 with dimethylethanolamine to obtain a polyacrylate emulsion; (2) The polyacrylate emulsion and 3,5-di-tert-butyl-4-hydroxybenzyl alcohol were mixed uniformly in a mass ratio of 12:1, and then 0.015 times the mass of the polyacrylate emulsion of sodium acetate was added, and the mixture was stirred at 250 r / min for 11 hours at 215°C under nitrogen protection, and then cooled to room temperature to obtain a UV absorbing polyacrylate emulsion; (3) acrylic acid, propylene glycol, xylene and azobisisobutyronitrile were mixed in a molar ratio of 5:1:30:0.04, stirred at 135°C and 250 r / min for 5 h, heated to 150°C, and reacted for 120 min to obtain a polyacrylic acid emulsion; (4) Using UV-absorbing polyacrylate emulsion as the shell solution, the liquid flow rate is 1 ml / h; using polyacrylic acid emulsion as the core solution, the liquid flow rate is 0.25 ml / h, and electrospinning is performed; the liquid flow rate is 0.25 ml / h, the receiving distance is 15 cm, the receiving speed is 10 r / min, and the spinning voltage is 24 kV; standing for 7 hours, and naturally cooling to room temperature to obtain anti-aging fibers.
[0027] Comparative Example 6 A method for preparing anti-aging fiber mainly comprises the following preparation steps: (1) Methyl methacrylate, diethyl allyl phosphate, isooctyl acrylate, methyl methacrylate, methacrylate and butyl acrylate were mixed in a mass ratio of 9:3:5:6:14 to obtain an olefin mixture; 1-allyl-1H-pyrrole, pyrrole and 1-(dimethylamino)pyrrole were mixed in a mass ratio of 1:4:1 to obtain a pyrrole mixture; the pyrrole mixture, olefin mixture, xylene, azobisisobutyronitrile and ferric chloride were mixed in a mass ratio of 1:5:30:0.04:0.04, stirred at 135°C and 250 r / min for 5 h, heated to 150°C, reacted for 120 min, and then the pH was adjusted to 7 with dimethylethanolamine to obtain a polyacrylate emulsion; (2) The polyacrylate emulsion and 3,5-di-tert-butyl-4-hydroxybenzyl alcohol were mixed uniformly in a mass ratio of 12:1, and then 0.015 times the mass of the polyacrylate emulsion of sodium acetate was added, and the mixture was stirred at 250 r / min for 11 hours at 215°C under nitrogen protection, and then cooled to room temperature to obtain a UV absorbing polyacrylate emulsion; (3) Electrospinning the UV-absorbing polyacrylate emulsion; the liquid flow rate is 0.25 ml / h, the receiving distance is 15 cm, the receiving speed is 10 r / min, and the spinning voltage is 24 kV; standing for 7 hours, and naturally cooling to room temperature to obtain anti-aging fibers.
[0028] Test Example 1 Flame retardancy test The limiting oxygen index was tested according to GB / T2406 test standard. The results are shown in Table 1.
[0029] Table 1
[0030] From the comparison of the experimental data in Table 1, it can be found that the anti-aging fiber prepared by the present invention has good flame retardancy.
[0031] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 1, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 1, which shows that polypyrrole can decompose to produce non-combustible gas after absorbing heat, which can dilute the concentration of oxygen in the air and combustibles produced by thermal decomposition of polymers on the one hand, and the nitrogen oxides produced by decomposition can capture free radicals and inhibit the chain reaction of polymers, thereby improving the flame retardancy of the material and increasing the limiting oxygen index of the material; From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 2, it can be found that the limiting oxygen index of Examples 1, 2, 3 is larger than that of Comparative Example 2, which shows that the phosphate ester can react chemically with the active free radicals generated during the combustion process, thereby inhibiting the generation and conduction of free radicals and preventing the effective contact between oxygen and the combustion material, which can reduce the activity of the surface of the combustion material, slow down the formation of flames and the rate of combustion reaction, thereby playing a flame retardant role. At the same time, organic phosphorus can also release a large amount of phosphorus-containing compounds during the combustion process. These compounds can generate phosphates with carbon on the surface of the combustion material at high temperature to form a phosphate protective layer, which covers the surface of the combustion material and plays a role of heat insulation and oxygen isolation, preventing the combustion material from continuing to burn, thereby improving the flame retardant ability of the material and increasing the limiting oxygen index of the material.
[0032] Test Example 2 Anti-aging test Anti-aging test: The artificial accelerated light aging test was carried out according to ISO4892-3 international standard, using fluorescent ultraviolet lamp UV-A340. After 15 days of irradiation, the fiber tensile strength was tested using a YG061F electronic single yarn strength tester. The test standard was GB / T14344, and the tensile fracture retention rate was calculated, where the tensile fracture retention rate = tensile fracture strength after aging treatment / tensile fracture strength before aging treatment * 100%. The results are shown in Table 2.
[0033] Table 2
[0034] From the comparison of the experimental data in Table 2, it can be found that the anti-aging fiber prepared by the present invention has good anti-aging ability.
[0035] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 4 in Table 2, it can be found that the fracture retention rates of Examples 1, 2, 3 are greater than those of Comparative Example 4, which shows that 3,5-di-tert-butyl-4-hydroxybenzyl alcohol is a hindered phenol, and the hydroxyl group is restricted by spatial barriers, and the hydrogen atom is very easy to fall off from the original molecular structure to achieve the proton-donating effect and combine with peroxy radicals, alkyl radicals, hydroxyl radicals, etc., resulting in the loss of the original activity and the termination of the oxygen aging reaction, thereby achieving the anti-aging effect and increasing the fracture retention rate of the material.
[0036] Test Example 3 Antistatic test The surface resistivity of the samples was measured using a surface resistance tester. The results are shown in Table 3.
[0037] Table 3
[0038] From the comparison of the experimental data in Table 3, it can be found that the anti-aging fiber prepared by the present invention has good antistatic ability.
[0039] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 1 in Table 3, it can be found that the surface resistivity of Examples 1, 2, 3 is lower than that of Comparative Example 1, which shows that polypyrrole, as a conductive polymer, can absorb and disperse static charges, thereby reducing the accumulation of static electricity, achieving an antistatic effect, and reducing the surface resistivity of the material.
[0040] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3, it can be found that the surface resistivity of Examples 1, 2, 3 is lower than that of Comparative Example 3, which shows that the quaternary ammonium salt has a hydrophilic group and a non-polar group, which enables it to absorb moisture in the air. This hygroscopicity helps to reduce the resistivity of the material surface.
[0041] Test Example 4 Antimicrobial testing The fiber was tested according to the GB / T20944 oscillation method, where the selected bacteria were Staphylococcus aureus and Escherichia coli. The results are shown in Table 4.
[0042] Table 4
[0043] From the comparison of the experimental data in Table 4, it can be found that the bio-based antibacterial fiber prepared in the present invention has good antibacterial ability.
[0044] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3 in Table 4, it can be found that the antibacterial rates of Examples 1, 2, 3 are higher than those of Comparative Example 3, which indicates that the quaternary ammonium cation adsorbs negatively charged bacteria through electrostatic force, hydrogen bonding force and hydrophobic binding between surfactant molecules and protein molecules, and accumulates on the cell wall to produce a chamber barrier effect, resulting in the inhibition of bacterial growth and death; at the same time, its hydrophobic alkyl group can also react with the hydrophilic group of the bacteria to change the permeability of the membrane, and then lyse the cell, destroy the cell structure, cause the dissolution and death of the cell, achieve the antibacterial effect, and enhance the antibacterial ability of the material.
[0045] Test Example 5 Moisture absorption test The water absorption rate was tested according to the national standard GB / T21655.1-2008, where water absorption rate = (mass after water absorption - initial mass) / initial mass * 100%. The results are shown in Table 5.
[0046] Table 5
[0047] From the comparison of the experimental data in Table 5, it can be found that the anti-aging fiber prepared by the present invention has good moisture absorption capacity.
[0048] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 3 in Table 5, it can be found that the water absorption rate of Examples 1, 2, 3 is greater than that of Comparative Example 3, which shows that the quaternary ammonium salt has a hydrophilic group that can absorb moisture in the air and achieve a good moisture absorption effect.
[0049] From the comparison of the experimental data of Examples 1, 2, 3 and Comparative Example 6, it can be found that the water absorption rates of Examples 1, 2, 3 are greater than that of Comparative Example 6, which indicates that the carboxyl group, as a hydrophilic group, can achieve a good moisture absorption effect.
[0050] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. An anti-aging fiber, characterized in that: The anti-aging fiber is prepared by coaxial electrostatic spinning of polyacrylic acid emulsion and ultraviolet absorption polyacrylate emulsion; The polyacrylic acid emulsion is prepared by polymerizing acrylic acid, propylene glycol and propenyl-1,3-sultone; The ultraviolet absorbing polyacrylate emulsion is prepared by polymerizing a pyrrole mixed liquid and an olefin mixed liquid and then reacting the mixture with 3,5-di-tert-butyl-4-hydroxybenzyl alcohol.
2. A method for preparing anti-aging fiber, characterized in that: The preparation method of the anti-aging fiber mainly includes the following preparation steps: (1) Mix the pyrrole mixed solution, olefin mixed solution, xylene and catalyst in a mass ratio of 1:4-6:25-35:0.06-0.1, stir at 130-140°C and 200-300 r / min for 4-6 hours, heat to 145-155°C, continue to react for 100-140 minutes, and then adjust the pH to 6.5-7.5 with dimethylethanolamine to obtain a polyacrylate emulsion; (2) The polyacrylate emulsion and 3,5-di-tert-butyl-4-hydroxybenzyl alcohol were mixed uniformly in a mass ratio of 10 to 14:1, and then 0.01 to 0.02 times the mass of the polyacrylate emulsion was added with sodium acetate, and the mixture was stirred at 210 to 220°C, 200 to 300 r / min, and reacted for 10 to 12 hours under nitrogen protection, and then cooled to room temperature to obtain a UV absorbing polyacrylate emulsion; (3) Mix acrylic acid, propylene glycol, xylene and azobisisobutyronitrile in a molar ratio of 4-6:1:25-35:0.03-0.05, stir at 130-140°C and 200-300 r / min for 4-6 hours, heat to 145-155°C, add propylene glycol and an amount of propenyl-1,3-sultone of the same mass, and continue the reaction for 100-140 minutes to obtain a polyacrylic acid emulsion; (4) Using UV-absorbing polyacrylate emulsion as the shell solution and polyacrylic acid emulsion as the core solution, coaxial electrospinning was performed, the fibers were allowed to stand for 6 to 8 hours, and then naturally cooled to room temperature to obtain anti-aging fibers.
3. The method for preparing an anti-aging fiber according to claim 2, characterized in that: The olefin mixed solution in step (1) is prepared by uniformly mixing methyl methacrylate, diethyl allyl phosphate, isooctyl acrylate, methyl methacrylate, methacrylate and butyl acrylate in a mass ratio of 8-10:2-4:4-6:5-7:12-16.
4. The method for preparing an anti-aging fiber according to claim 2, characterized in that: The pyrrole mixture in step (1) is prepared by uniformly mixing 1-allyl-1H-pyrrole, pyrrole and 1-(dimethylamino)pyrrole in a mass ratio of 1:3 to 5:
1.
5. The method for preparing an anti-aging fiber according to claim 2, characterized in that: The catalyst in step (1) is prepared by mixing azobisisobutyronitrile and ferric chloride in a mass ratio of 1:
1.
6. The method for preparing an anti-aging fiber according to claim 2, characterized in that: The liquid flow rate of the shell solution in step (4) is 0.9-1.1 ml / h.
7. The method for preparing an anti-aging fiber according to claim 2, characterized in that: The liquid flow rate of the core solution in step (4) is 0.2-0.3 ml / h.
8. The method for preparing an anti-aging fiber according to claim 2, characterized in that: The coaxial electrospinning parameters of step (4) are as follows: liquid flow rate of 0.2-0.3 ml / h, receiving distance of 14-16 cm, receiving speed of 9-11 r / min, and spinning voltage of 22-26 kV.
Citation Information
Patent Citations
Process of treatment of fibers and / or textile materials
CN102822413A
High-toughness waterproof material formula
CN108587371A
Preparation method and application of electrospinning nanofiber
CN108866820A
Anti-aging nano-zinc oxide modified polylactic acid fiber and preparation method thereof
CN113430673A
Nanofiber membrane as well as raw materials, preparation method and application thereof
CN116355289A
